Abundant expression and purification of biologically active mitochondrial citrate carrier in baculovirus-infected insect cells. - M. Madeo; C. Carrisi; D. Iacopetta; A. R. Cappello; F. Palmieri; G. Mazzeo; A. Montalto; V. Dolce; CAPOBIANCO, Loredana; BUCCI, Cecilia (Journal of Bioenergetics and Biomembranes, 2009)
Heterologous expression of recombinant proteins is an essential technology for protein characterization. A major obstacle to investigating the biochemical properties of membrane proteins is the difficulty in obtaining sufficient amounts of functional protein. Here we report the successful expression of the tricarboxylate (or citrate) carrier (CIC) of eel (Anguilla anguilla) from Spodoptera frugiperda (Sf9) cells using the baculovirus expression system. The recombinant CIC was purified by affinity chromatography on Ni2+-NTA agarose; the yield of the purified active protein was 0.4–0.5 mg/l of culture. The transport characteristics of the recombinant CIC and the effects of inhibitors on transport are similar to those determined for eel liver mitochondrial CIC. Because the CIC is one member of an extensive family of mitochondrial transport proteins, it is likely that the procedure used in this study to express and purify this carrier can be successfully applied to other mitochondrial transport proteins, thus providing sufficient protein for functional characterization.